User-Centred Subtitling: Usability as an Assessment and Process Framework for Interlingual Subtitles - Tuominen, Tiina (Journal of Audiovisual Translation, 2025)
The audience’s perspective is often prominent in evaluating subtitle quality, with concepts such as readability being used as assessment criteria. In audiovisual translation research, reception studies have become a visible presence. Understanding the audience is thus clearly central for both research and practice, but information on actual audience preferences does not always filter through to subtitling practice or to quality assessment. Therefore, there seems to be a need for a model that could support the existing audience orientation and make the audience’s perspective a consistent consideration throughout the subtitling process. This article proposes the concept of usability as a framework for an audience-oriented view of interlingual subtitling. The article introduces the usability-based user-centred translation (UCT) model and discusses how it could be applied to subtitling practice. In addition, it explores the differences and similarities between UCT and existing practices in the media localisation industry. This comparison aims to demonstrate how UCT could be implemented in the industry, what added benefit it might bring in comparison to current practices, and how it could fit into existing workflows. Lay summary In subtitling, quality is often defined by how well the audience is able to understand and enjoy a programme with the support of subtitles. The audience is also central in audiovisual translation research, and there are numerous reception studies on many aspects of reading and understanding subtitles. However, it can be difficult for practitioners to find out how best to serve the viewers, as information and research findings about audiences may be difficult to access. Therefore, we need new ways of applying information about audiences into subtitling practice. This article proposes that subtitles could be thought of as a text that is used to achieve a specific goal, which is to understand the subtitled programme. Subtitles could therefore be assessed in terms of their usability. Employing the concept of usability could help make the audience a more constant presence in subtitling, shed light on which aspects of subtitles affect the viewing experience, and clarify what information subtitlers need so that they can create usable subtitles. The article introduces the model of user-centred translation (UCT), which provides practical tools for improving the usability of translations. The article demonstrates how UCT can be applied to subtitling, how the UCT model differs from current industry practices, and how those practices could be made more user-centred.